Analysis Of Income And Feasibility Of Msmes In Watutau Village, Poso District (Case Study On: Alamanda Accessories Craftsman Business) - Abd Fazry; Andi Herman Jaya; Edhi Taqwa; Muhtar Lutfi; Musdayati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to analyze: the amount of business income in the Alamanda Craftsmen business, the feasibility of the business in the Alamanda Accessories Craftsmen Business. This research was conducted in Watutau Village, Lore Peore District, Poso Regency, from December 2023 to February 2024. The research method used was a descriptive method. The data collected includes secondary data and primary data. Primary data was obtained by direct interviews with Alamanda Accessories Crafts business owners, while secondary data was obtained from books and financial reports. The data analysis used is analysis including production costs, income, business feasibility in the Alamanda Accessories Craftsman Business, Lore Peore District. The research results show that the monthly production costs of the business include fixed costs of IDR 3,228,333, variable costs of IDR 20,010,000, total costs of IDR 23,238,333, while the monthly net income of the Alamanda Accessories Craftsmen business is IDR 14,761,667. Feasibility of the Alamanda Accessories Craftsman Business, Lore Peore District, Watutau Village, Poso Regency, can be said to be feasible to operate with an R/C Ratio of 1.6.